SURVEI ANTROPOMETRI DANKEMAMPUAN MOTORIK SISWA KELAS II SDN LEMPER I PADEMAWU - Rizal Firmansyah Putra (STKIP PGRI SUMENEP, 2020)
This study aims to determine: 1) anthropometric survey of the second grade students at Elementary School of Lemper I Pademawu; 2) the motor ability of the second grade students at Elementary School of Lemper I Pademawu. The sample in this study used a purposive sampling method. Data processing in this study used the Correlation Coefficient analysis with Microsoft Excel. Based on the results of the study showed that 1) anthropometric survey of the second grade students at Elementary School of Lemper I Pademawu based on the results of body mass index (BMI) analysis is average of 18.12 kg/m2 which included in the category of light underweight with details of 21.87% were light underweight, 40.62% were underweight, and 47.5% were in the normal category. 2)The motor ability of the second grade students at Elementary School of Lemper I Pademawu which included a 30 meter sprint test, long jump without prefix, balance, and average agility included in the